Community-managed groundwater irrigation on the Vientiane Plain of Lao PDR: planning, implementation and findings from a pilot trial - Clement, C.; Vinckevleugel, Jordan; Pavelic, Paul; Xiong, K.; Valee, L.; Sotoukee, T.; Shivakoti, B. R.; Vongsathien, K. (International Water Management Institute, 2018)
Laos has vast surface water resources. However, in areas located far away from surface water sources or those that are prone to surface water scarcity, groundwater is gaining recognition as a valuable source of water for agricultural development. Households in Ekxang village on the Vientiane Plain, for example, depend on rainfall for the cultivation of rice during the wet season and a wide range of vegetables and herbs in the dry season. Climate change poses a growing threat to crop production in such villages, altering wet season rainfall and making drought more common and severe. To help find a new way forward, a 2-year pilot study of groundwater irrigation was carried out in Ekxang to assess the technical performance, economic viability and effectiveness of the institutional arrangements. Participation in the pilot was quite modest due to farmers being wary of possible risks related to the costs of the new irrigation system. As farmers gained experience with the high-performance pumps and other equipment, their trust grew, and they came to have a sense of ownership over the system. The irrigation system turned out to be profitable for dry-season irrigation of cash crops. Growing rice under these conditions proved to be unprofitable. Increased profits, however, did not translate into increased popularity. In the pilot’s second year, with the subsidy removed, participation in the groundwater users group declined. Apart from the additional cost for pumping, another reason was a lack of household labor to manage the production of cash crops under groundwater irrigation. This, in turn, stemmed from the availability of other livelihood options (such as small businesses and wage labor), which compete with agriculture and may prove more appealing. Clearly, the future development of such systems will depend, not just on local hydrogeological conditions, but also on a better understanding of the social and economic factors that influence farmers’ decisions. New technologies could make a difference as well, such as solar pumps, which likely reduce farmers’ production costs. Lessons learned from this pilot study should prove valuable for helping realize the potential of groundwater irrigation in Laos.